Recent progress on the utilization of waste heat for desalination: A review. (1st October 2020) - Elsaid, Khaled; Taha Sayed, Enas; Yousef, Bashria A.A.; Kamal Hussien Rabaia, Malek; Ali Abdelkareem, Mohammad; Olabi, A.G.
Graphical abstract: Highlights: 20–50% of the energy used in industrial sector is wasted as heat. Technical feasibility of waste heat to drive desalination processes is proven. Low-energy demand emerging desalination process has a higher potential. Utilization of waste heat has proven reduction in desalination cost and environmental impacts. Abstract: Desalination is currently considered as a reliable nonconventional freshwater supply, which has been practiced on a large scale for many decades. Nevertheless, desalination is generally the most energy-intensive and costly water treatment process. The current desalination capacity of 38 billion cubic meters per day (BCM/d), consuming energy of almost 75 TWh. Fossil fuel, such as coal, oil, and gas, is the primary energy source to drive different desalination processes for both thermal and electrical energy demand. However, the extensive use of fossil fuel has been related to global warming and climate change, hence raised many calls to reduce its consumption, develop high-efficiency energy processes, and better utilization of fuel and energy. It has been estimated that 20–50% of the energy used globally is wasted as heat; thus, it represents a good opportunity for energy recovery, both quantitatively and qualitatively. Waste heat (WH) has a high potential to fully or partially drive different desalination processes either as heat or after recovery and conversion into electrical or mechanical energy forms. This review is the first of its type to discuss the effort in utilizing WH in desalination processes and its recent advances. The review discusses the WH sources and types, as well as recovery systems relative to their utilization in desalination processes. Then the different desalination processes relative to their potential to be driven by WH utilization are thoroughly discussed, with focus is being given to emerging desalination due to the many benefits driving their development. It was found that WH has successfully been used to drive different desalination processes, with the main effort given to the direct utilization of heat to drive different thermally-driven desalination processes. The utilization of WH has proven to bring significant economic and environmental benefits hence lowering desalination cost and associated greenhouse gases (GHGs) emissions. Other mechanically-driven, and electrically-driven processes, can be found in the contexts of waste-to-power energy recovery systems, which can be later used to drive such processes. Although WH has been successfully employed for desalination, we conclude that still more efforts need for research, development, and demonstration (RD&D) in this field, which should be addressed in the near future as it presents a good opportunity to secure energy supply for increasing water demand.